ANALISIS HUKUM TERHADAP PENYEDIAAN PRASARANA KESELAMATAN PENGUNJUNG PARIWISATA DI PANTAI AKKARENA - Nataniel Nataniel; Muhammad Halwan; Zulkifli Makkawaru (IAIN Palopo, 2022)
This study aims to determine the form of providing visitor safety infrastructure at Akkarena Beach and the factors that are an obstacle for safety infrastructure providers, so that there are no cases of drowning visitors at Akkarena Beach. The type of research used is normative-empirical. The research location is at Akkarena Beach, Jalan Metro Tanjung Bunga. Data sources are primary and secondary. Data collection techniques were carried out by field observations, interviews, and field checklists. The data obtained in this study were then analyzed descriptively-qualitatively.The results show that the form of providing safety infrastructure at Akkarena Beach in general has met the security and safety requirements based on the reference to the Australian Coastal Public Safety Guidelines, and tourism facilities have met the standards to meet the needs of tourism visitors, as well as changing room and toilet facilities that meet safety standards. based on the reference to the Indonesian Toilet Association, but there are some safety facilities that are still incomplete and need to be replaced because they are no longer suitable for use. Several inhibiting factors for the provision of safety infrastructure so that there are no cases of drowning visitors at Akkarena Beach include the negligence of parents, not using safety equipment when carrying out water activities, not heeding the instructions of the coast guard, disease factors, and weather which often causes drowning accidents